Rice protein phosphatase 1 regulatory subunits OsINH2 and OsINH3 participate actively in growth and adaptive responses under abscisic acid - Jadoon, Sawaira; Qin, Qianqian; Shi, Weiqiang; Longfeng, Yan; Hou, Suiwen (Frontiers in Plant Science, 2022)
Rice (Oryza sativa. L), a worldwide staple food crop, is affected by various environmental stressors that ultimately reduce yield. However, diversified physiological and molecular responses enable it to cope with adverse factors. It includes the integration of numerous signaling in which protein phosphatase 1 (PP1) plays a pivotal role. Research on PP1 has been mostly limited to the PP1 catalytic subunit. in numerous cellular progressions. Therefore, we focused on the role of PP1 regulatory subunits (PP1r), OsINH2 and OsINH3, homologs of AtINH2 and AtINH3 in Arabidopsis, in rice growth and stress adaptations. Our observations revealed that these are ubiquitously expressed regulatory subunits that interacted and colocalized with their counter partners, type one protein phosphatase (OsTOPPs) but couldn’t change their subcellular localization. The mutation in OsINH2 and OsINH3 reduced pollen viability, thereby effected rice fertility. They were involved in abscisic acid (ABA) mediated inhibition of seed germination, perhaps by interacting with osmotic stress/ABA-activated protein kinases (OsSAPKs). Meanwhile, they positively participated in osmotic adjustment by proline biosynthesis, detoxifying reactive oxygen species (ROS) through peroxidases (POD), reducing malondialdehyde formation (MDA), and regulating stress-responsive genes. Moreover, their co-interaction proposed they might mediate cellular processes together or by co-regulation however, the special behavior of two different PP1r is needed to explore. In a nutshell, this research enlightened the involvement of OsINH2 and OsINH3 in the reproductive growth of rice and adaptive strategies under stress. Hence their genetic interaction with ABA components and deep mechanisms underlying osmotic regulation and ROS adjustment would explain their role in complex signaling. This research offers the basis for introducing stress-resistant crops.